Determination of content of ascorbic acid on camu camu drying liofilization - Reyna M., L. (2013)
The results of research, we allow see, the speed of the cooling and warning considerate the difference of mass loaded and diseing of the equipment for to cool and to heat the camu camu mass. The dry product in each case have pink color, suitables aroma and flavor, good solubility, whit moisture less tan to 10 %. The difference of ascorbic acid contens in the fresh pulp and the dry samples is 22,75 mg, thus the most difference is 19,8 mg for the dry samples for 100 g of simple. The dry product characteristics would to used for to produce ice cream, nectar, extract, drink fortifies will permit the development zone agrarian